2016
DOI: 10.1111/ajo.12451
|View full text |Cite
|
Sign up to set email alerts
|

Gestational surrogacy in Australia 2004-2011: treatment, pregnancy and birth outcomes

Abstract: To avoid adverse outcomes for both carriers and babies, SET should be advocated in all gestational surrogacy arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In surrogacy, a third party is used as a pregnancy carrier who becomes pregnant for an intended couple. [ 4 ] This third party, who is the surrogate mother, becomes pregnant with the knowledge that she must delegate all parental rights to parents who own the fetus. [ 5 ] The most common indications of the surrogacy include the uterine absence, recurrent pregnancy loss, recurrent in vitro fertilization (IVF) failure, dangerous obstetric and medical conditions result in high-risk pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In surrogacy, a third party is used as a pregnancy carrier who becomes pregnant for an intended couple. [ 4 ] This third party, who is the surrogate mother, becomes pregnant with the knowledge that she must delegate all parental rights to parents who own the fetus. [ 5 ] The most common indications of the surrogacy include the uterine absence, recurrent pregnancy loss, recurrent in vitro fertilization (IVF) failure, dangerous obstetric and medical conditions result in high-risk pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“… 104 105 Also, double embryo transfers are quite common in surrogate processes, because it is usually cheaper than having two separate pregnancies, resulting in more multiple pregnancies. 106 107 108 109 In addition, it is believed that cesarean section rates are high among surrogates, not only because IPs may ask for it, but also because low-income surrogates receive medical care in private clinics while in other situation they would be treated in public health systems. 110 Candidates to |GC are often quite misinformed about the procedure and lack of psychological and legal support.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…The number of the embryos transferred is characterized by controversy and debate. Numerous studies support the elective single embryo transfer (eSET), especially in cases of surrogacy, as the most efficient approach to limit multiple gestation and preterm birth, which are both accompanied by adverse perinatal and neonatal outcomes [ 4 , 7 , 36 ]. The elective single embryo transfer is embraced universally as the optimal method associated with the best perinatal and neonatal outcomes.…”
Section: Risk Factors Regarding the Preimplantation Embryo Of A Sumentioning
confidence: 99%
“…In contradiction to natural conceptions, pregnancies deriving from ART cycles—including surrogacy cycles—may be related to increased risk of perinatal complications. It has been indicated that the perinatal outcomes of gestational surrogacy in comparison to autologous IVF report no major increase in the risks of preterm birth, live birth rate, and congenital anomalies [ 4 ]. In addition to that, it was contemplated that oocyte donation demonstrates poor fetal immunological adjustment to allogeneic antigen.…”
Section: Risk Factors Related To the Gestation And The Fetusmentioning
confidence: 99%
See 1 more Smart Citation